2012
DOI: 10.1128/iai.00086-12
|View full text |Cite
|
Sign up to set email alerts
|

The Yfe and Feo Transporters Are Involved in Microaerobic Growth and Virulence of Yersinia pestis in Bubonic Plague

Abstract: The Yfe/Sit and Feo transport systems are important for the growth of a variety of bacteria. In Yersinia pestis, single mutations in either yfe or feo result in reduced growth under static (limited aeration), iron-chelated conditions, while a yfe feo double mutant has a more severe growth defect. These growth defects were not observed when bacteria were grown under aerobic conditions or in strains capable of producing the siderophore yersiniabactin (Ybt) and the putative ferrous transporter FetMP. Both fetP an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
108
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(110 citation statements)
references
References 91 publications
2
108
0
Order By: Relevance
“…Available data does not currently support the transcriptional regulator model, and we could not detect KpFeoC binding to DNA using the gel-shift or SELEX experiments (20,22); evidence supporting the G-protein modulator model is lacking. The protease inhibitor model appeared to be the only model supported by in vivo data.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Available data does not currently support the transcriptional regulator model, and we could not detect KpFeoC binding to DNA using the gel-shift or SELEX experiments (20,22); evidence supporting the G-protein modulator model is lacking. The protease inhibitor model appeared to be the only model supported by in vivo data.…”
Section: Discussionmentioning
confidence: 81%
“…Thus, FeoC was proposed to be an ironsulfur cluster-dependent transcriptional regulator directly controlling the expression of the feo operon (transcriptional regulator model) (6). However, a recent study suggested that FeoC did not regulate the feo promoter in Yersinia pestis (20), and no report has confirmed the DNA binding activity of FeoC.…”
mentioning
confidence: 92%
“…Y. pestis has multiple ferrous iron transporters, including Feo, Yfe, and Fet. These do not appear to be redundant, as mutations in either feo or yfe resulted in a significant growth defect (45). Similarly, Bordetella pertussis uses different systems at different times during infection (46).…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of these features, the FeoC protein was initially proposed as a Fe-S cluster-dependent transcription factor controlling the feo operon (2); however, a feoC mutation was shown to have no effect on transcription of the feo promoter in Yersinia pestis (7). Nonetheless, evidence suggests that the FeoC protein plays a role as the FeoB transporter, because the FeoC protein and the N-terminal domain of FeoB from Klebsiella pneumoniae were shown to interact with each other (8).…”
mentioning
confidence: 99%